Ethnicity and power in the contemporary world - Rupesinghe, Kumar; Tishkov, V. A. (Valeriĭ Aleksandrovich), 1941- (United Nations University Press, 1996)
"Scholars from Africa, Europe, Asia, and North America explore conflicts and conflict resolution approaches in regions of the former Soviet Union, the Horn of Africa, India, the Basque region of Spain, the former Yugoslavia, Northern Ireland, and the United States."--Publisher's description